Lumbar malignant peripheral nerve sheath tumor: a rare case in a young patient - Paparella, Maria Teresa; Eusebi, Laura; Mazzucchelli, Roberta; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Malignant peripheral nerve sheath tumor (MPNST) is a rare soft tissue sarcoma that originate from peripheral nerves or from cells associated with the nerve sheath. We report the case of a 30‑year‑old male patient with a history of neurofibromatosis type I (NF-1) and a MPNST located in the lumbar region. The mass was resecated but surgical margins weren’t clear. Recurrence of disease was observed after few months. A close monitoring of subjects with NF-1 is crucial to diagnose MPNST at an earlier stage and allow a complete surgical resection.